INNOVATIVE TECHNOLOGY with MICRO-IRRIGATION for SUSTAINABLE FARMING in HILLS - Dangwal, A. Kiran Kumar; Mehta, B. Deepa (International Journal of Psychosocial Rehabilitation, 2020)
A vast tract of land inhabited by humans consists of hilly terrain. The people from these hills, per force, resort to terrace cultivation. Water for irrigation is not scarce but mis-managed. Whatever the scant rainfall it receives is allowed to run down the slopes unutilised. No substantial effort is made to enrich the moisture content of the soil or recharge the subsoil water. The water is wasted down through rivulets and streams. The sub Himalayan region is blessed with a string of rivers. Billions of cfs of water just flows down to the plains. No environment friendly efforts are made to harness the energy from this flowing water at micro level. Using conventional means of irrigation by pumps and motors is neither sustainable nor economical. Thus the lack of cultivation is leading to mass migration to big cities in plains for alternate livelihood. Only the old and handicapped persons are left behind to fend for themselves. This in turn is resulting in demographic shift and overcrowding of cities. The village land is lying virtually abandoned in most hilly areas. This paper dwells on utilising and upgrading with newer technology the potentials 0f natural energy sources available in situ. These sources are the gravitational flow of water, barometric pressure, solar and wind energy. The paper also highlights the adoption of rain harvesting techniques and promotion of micro-irrigation by resorting to capillary and drip irrigation for sustainable development.